Environmental pollution challenges public health surveillance: the case of mercury exposure and intoxication in Brazil - Maria Elena Crespo-Lopez; Amanda Lopes-Araújo; Paulo Cesar Basta; Isabela Soares-Silva; Carlos B.A. de Souza; Caio Gustavo Leal-Nazaré; Letícia Santos-Sacramento; Jean Ludger Barthelemy; Gabriela P. Arrifano; Marcus Augusto-Oliveira (Elsevier, 2024)
Summary: Pollution, causing millions of deaths annually, disproportionally affects low- and middle-income countries (LMICs). Mercury ranks among the three main chemicals of major public health concern, and even low levels can cause cardiovascular and nervous outcomes, with children and indigenous populations being especially vulnerable. Nearly 80% of all emissions in South America originate from the Amazon. Brazil, the fifth-largest contributor to global mercury emissions, exemplifies the challenges faced by LMICs in effectively monitoring and addressing mercury exposure/intoxication. Despite having powerful tools such as SINAN (a digital platform for compulsory disease reporting), and Community Health Agents, data reveals significant underreporting, especially in the Amazon. Furthermore, SINAN has important delays in its update: for instance, 196 cases of Munduruku Indigenous people in 2019 have only been included in 2023. In this Personal View, we outline insightful recommendations to enhance public health surveillance and implement enduring, effective strategies to monitor, report and address mercury exposure/intoxication, focusing on the Brazilian Amazon. Although these recommendations are tailored to the challenges of this country, they hold potential for adaptation by other Amazonian countries facing similar issues (high mercury emissions and the presence of vulnerable populations, among others).